Discovery of 1, 3-dihydro-2H-imidazo[4, 5-c]quinolin-2-ones based novel, potent and PI3Kδ selective inhibitors. Issue 11 (1st June 2019) - Bahekar, Rajesh; Dave, Bhushan; Soman, Shubhangi; Patel, Dipam; Chopade, Rajendra; Funde, Radhika; Kumar, Jeevan; Sachchidanand, S.; Giri, Poonam; Chatterjee, Abhijit; Mahapatra, Jogeswar; Vyas, Purvi; et al.
Graphical abstract: Abstract: PI3Kδ is implicated in various inflammatory and autoimmune diseases. For the effective treatment of chronic immunological disorders such as rheumatoid arthritis, it is essential to develop isoform selective PI3Kδ inhibitors. Structure guided optimization of an imidazo-quinolinones based pan-PI3K/ m -TOR inhibitor (Dactolisib) led to the discovery of a potent and orally bioavailable PI3K δ isoform selective inhibitor (10h ), with an improved efficacy in the animal models.